MEMBELAJARKAN KETERAMPILAN BERKOMUNIKASI SEJAK DINI - Putu Eka Sastrika Ayu (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Instead of hardskills, todays, communication skill is one of the most important softskillsthat leads people getting success in their life. Hence, the communication skills should be learntby students from the beginning of their school periods. This study was purposed to discuss howto train the elementary school students the communication skills integrated with their subjectmatter learning as a part of developing not only the competitive human resourcers but alsohaving good character. The effective communication for elementary school learning was firstlydiscussed through literature search study, and two strategic ways to improve communicationskills were analyzed. Two strategic ways are considered to improve the learning of communicationskills at elementary school i.e. through (1) the applying strategies, models and methods of learningthat can efectively optimize the learning and training of communication skills, and (2) improvingthe effective communication based teaching basic skills of elementary teachers.